El sistema de poljes de la región de Dystos-Almyropotamos (Isla de Eubea, Grecia): Cartografía y evolución geomorfológica - Peña-Monné, J.L.; De Dapper, M.; Constante, A.; De Vliegher, B.; Pavlopoulos, K. (Geographicalia, 2015)
A geomorphological mapping of a karstic area developed on marblesand schists in the central sector of the island of Eubea is presented. The systemof poljes constitutes the main geomorphological feature. It is related both to the geological structure and to the climatic evolution during the Quaternary. Only three out of the 12 poljes differentiated remain in closed conditions. These depressions display extensive planation surfaces and cones rocheux generated by karstic cryptocorrosion processes during different stages. On the other hand, remnants of older planation surfaces affected by karren and dolines have been identified in the summit areas. Finally, the proposed geomorphological evolutive model is related to other Mediterranean karstic areas.
Keywords: Greece; Karst; poljes; Quaternary.